Privacy Decision-making and the Effects of Privacy Choice Architecture - Experiments Toward the Design of Behaviorally-Aware Privacy Regulation - Christopher Jon Sprigman; Stephan Tontrup (SSRN, 2024)
The current notice and choice privacy framework fails to empower individuals in effectively making their own privacy choices. In this Article we offer evidence from three novel experiments showing that at the core of this failure is a cognitive error. Notice and choice caters to a heuristic that people employ to make privacy decisions. This heuristic is meant to distinguish between a party's good or bad intent in face-to-face-situations. In the online context, it distorts privacy decision- making and leaves potential disclosers vulnerable to exploitation. From our experimental evidence exploring the heuristic's effect, we conclude that privacy law must become more behaviorally aware. Specifically, privacy law must be redesigned to intervene in the cognitive mechanisms that keep individuals from making better privacy decisions. A behaviorally-aware privacy regime must centralize, standardize and simplify the framework for making privacy choices. To achieve these goals, we propose a master privacy template which requires consumers to define their privacy preferences in advance-doing so avoids presenting the consumer with a concrete counterparty, and this, in turn, prevents them from applying the intent heuristic and reduces many other biases 2 that affect privacy decision-making. Our data show that blocking the heuristic enables consumers to consider relevant privacy cues and be considerate of externalities their privacy decisions cause. The master privacy template provides a much more effective platform for regulation. Through the master template the regulator can set the standard for automated communication between user clients and website interfaces, a facility which we expect to enhance enforcement and competition about privacy terms..
Keywords: 330; Privacy; Heuristic to disclose personal data; Public Goods